Neural correlates of the reverse Simon effect in the Hedge and Marsh task. (August 2015) - Li, Hui; Xia, Tiansheng; Wang, Ling
Abstract: The Simon effect is a typical paradigm for investigating cognitive control in which participants respond faster and more accurately when the stimulus position corresponds to the response position (congruent) than when it does not (incongruent). However, Hedge and Marsh (1975) reported that the effect depended on task rules. Interestingly, the effect can be reversed (i.e., faster reaction time in the incongruent condition than in the congruent condition) when participants respond to the stimulus color by pressing the key labeled with an alternate color. A classic Simon effect is present when responding with the key possessing the same color as the stimulus. In the present study, we investigated the neural correlates of the Hedge and Marsh effect using functional magnetic resonance imaging (fMRI). We manipulated the overlap between the stimulus and response at both the perceptual and conceptual levels using physical color and Chinese pinyin as response labels. The behavioral results showed a classic Simon effect in the same-Color Mapping but a reversed Simon effect in the alternate-Color Mapping. The fMRI results revealed a main effect of Color Mapping: stronger activation in the dorsal frontoparietal regions (bilateral superior parietal lobule [SPL] and dorsal premotor cortex [dPMC]), pre-supplementary motor area (pre-SMA)/anterior midcingulate cortex (aMCC) and bilateral dorsolateral prefrontal cortex (DLPFC), as well as a stronger deactivation in the default mode network (bilateral inferior parietal lobule, posterior cingulate cortex and ventral medial prefrontal cortex) in the alternate-Color Mapping compared to the same-Color Mapping. More importantly, some of those areas, including the bilateral SPL/intraparietal sulcus and dPMC, pre-SMA/aMCC, bilateral DLPFC and bilateral temporoparietal junction, also showed an interaction between Color Mapping and Spatial Congruency: stronger activity in the incongruent than in the congruent condition in the same-Color Mapping but weaker activity in the alternate-Color Mapping, which was similar to the behavioral results. The brain activation pattern was similar in the color and pinyin sessions. The implications of these results for cognitive control are discussed. Highlights: The Hedge and Marsh (HM) effect exists at both perceptual and conceptual level. Superior parietal lobule and dorsal premotor cortex activity shows the HM effect. Medial and lateral prefrontal cortex activity also shows the HM effect. Anterior midcingulate cortex responds to the need for control in the HM effect. Superior parietal lobule represents interactions between color and spatial mapping.